m/4+6=m/3+8

Simple and best practice solution for m/4+6=m/3+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m/4+6=m/3+8 equation:


m in (-oo:+oo)

m/4+6 = m/3+8 // - m/3+8

m/4-(m/3)-8+6 = 0

-1/12*m-2 = 0 // + 2

-1/12*m = 2 // : -1/12

m = 2/(-1/12)

m = -24

m = -24

See similar equations:

| x^4-7x^3-30x^2=0 | | 1/2r+6=5 | | 6p - 5=2p+7+7 | | 5t-18=12+3x | | 1+4i/4-i | | -7x-16=-5x | | 15p^2=20+20p | | 3y/8-9=y/8 | | 10q+3(5-2q)+4(7q+4)= | | 5x/-4=6x/8 | | 4/15z=1/10-4/9 | | 2x+1x+1x=180 | | -1+5=m-8 | | -4.90x^2-2.25x+1.92=0 | | y=1/2(8-1) | | 45-15-5(y+10)= | | x^2+0.0201x-0.0078591=0 | | 135-4x=41x+15 | | 7x-4(x-1)-3= | | 2/5-m/9=7/45 | | 1/5a+8=9 | | 0.70x+0.70(50)=0.35(98) | | y/3=y/5+8 | | 4+9(4-6m)=0 | | R-0.03=1.65 | | F+1.25=12.90 | | 63x^2-67x-18=0 | | 9.09+S=13.64 | | 3y+19=5y-7 | | 9.09+S= | | 5/6x=-2/18 | | -2y+2=-2(3y+11) |

Equations solver categories